Segmentation and simulation of objects in pedobarography images using physical principles - Patrícia C. T. Gonçalves (2008)
The goals of the present work are to automatically extract the contour of an object and to simulate its deformation using a physical approach. Thus, to segment an object represented in an image, an initial contour is manually defined for it that will then automatically evolve until it equals the border of the desired object. The contour is modelled by a physical formulation, and its evolution to the desired final contour is driven by internal and external forces. To build the physical model of the contour used in the segmentation process, we adopted the isoparametric finite element proposed by Sclaroff, and to obtain its evolution towards the object border we used the methodology presented by Nastar that consists in solving the dynamic equilibrium equation between two consecutive instants. As for the simulation of the deformation between two different instances of an object, or between two objects, after their contours have been properly modelled, modal analysis, complemented with global optimization techniques, is employed to establish the correspondence between their nodes (data points). After the matching phase, the displacements field between the two contours is simulated using the dynamic equilibrium equation. The proposed approach will be here considered in dynamic pedobarography images.